Protein markers forCandida albicansEVs include claudin‐like Sur7 family proteins - Charlotte S. Dawson; Donovan Garcia‐Ceron; Harinda Rajapaksha; Pierre Faou; Mark R. Bleackley; Marilyn A. Anderson (2020)
ABSTRACT Background: Fungal extracellular vesicles (EVs) have been implicated in host‐pathogen and pathogen‐pathogen communication in some fungal diseases. In depth research into fungal EVs has been hindered by the lack of specific protein markers such as those found in mammalian EVs that have enabled sophisticated isolation and analysis techniques. Despite their role in fungal EV biogenesis, ESCRT proteins such as Vps23 (Tsg101) and Bro1 (ALIX) are not present as fungal EV cargo. Furthermore, tetraspanin homologs are yet to be identified in many fungi including the model yeast S. cerevisiae. Objective: We performed de novo identification of EV protein markers for the major human fungal pathogen Candida albicans with adherence to MISEV2018 guidelines. Materials and methods: EVs were isolated by differential ultracentrifugation from DAY286, ATCC90028 and ATCC10231 yeast cells, as well as DAY286 biofilms. Whole cell lysates (WCL) were also obtained from the EV‐releasing cells. Label‐free quantitative proteomics was performed to determine the set of proteins consistently enriched in EVs compared to WCL. Results: 47 proteins were consistently enriched in C. albicans EVs. We refined these to 22 putative C. albicans EV protein markers including the claudin‐like Sur7 family (Pfam: PF06687) proteins Sur7 and Evp1 (orf19.6741). A complementary set of 62 EV depleted proteins was selected as potential negative markers. Conclusions: The marker proteins for C. albicans EVs identified in this study will be useful tools for studies on EV biogenesis and cargo loading in C. albicans and potentially other fungal species and will also assist in elucidating the role of EVs in C. albicans pathogenesis. Many of the proteins identified as putative markers are fungal specific proteins indicating that the pathways of EV biogenesis and cargo loading may be specific to fungi, and that assumptions made based on studies in mammalian cells could be misleading. Abbreviations: A1 – ATCC10231; A9 – ATCC90028; DAY B – DAY286 biofilm; DAY Y – DAY286 yeast; EV – extracellular vesicle; Evp1 – extracellular vesicle protein 1 (orf19.6741); GO – gene ontology; Log 2 (FC) – log 2 (fold change); MCC – membrane compartment of Can1; MDS – multidimensional scaling; MISEV – minimal information for studies of EVs; sEVs – small EVs; SP – signal peptide; TEMs – tetraspanin enriched microdomains; TM – transmembrane; VDM – vesicle‐depleted medium; WCL – whole cell lysate